The Impact of Financial Development on Economic Growth in BRICS Countries - Motau, Tshepo; Wyk, Abigail Stiglingh-Van (International Journal of Economics and Financial Issues, 2026)
This study examines the impact of financial development on economic growth in the BRICS countries, Brazil, Russia, India, China, and South Africa over the period 2000 to 2024. It aims to determine how financial development contributes to growth in these emerging economies, which play an increasingly influential role in the global financial system. Drawing on literature emphasising capital accumulation, innovation, and financial intermediation, the study focuses on gross fixed capital formation, employment-to-population ratio, research and development expenditure, and domestic credit to the private sector. Using a quantitative panel data approach with fixed and random effects regression models, the Hausman test identifies the fixed-effects specification as most suitable, accounting for country-specific institutional and structural characteristics. Results show that gross fixed capital formation and research and development expenditure significantly boost GDP growth, highlighting the importance of investment and innovation, whereas financial development exhibits an insignificant or negative effect, reflecting inefficiencies in credit allocation and weak transmission to productive investment. The study concludes that financial development alone is insufficient for growth; sustainable expansion requires effective regulation, good governance, inclusive financial systems, and deeper capital markets across BRICS economies.